Accounting for international trade in value added: a comment on the OECD–WTO project. Issue 4 (2nd October 2018) - Reich, Utz-Peter
ABSTRACT: In the global economy of today, global value-added chains allow firms and countries to take apart the production process and do the part they are best at. In response to this new reality, OECD and WTO have launched a common statistics project of the 'OECD–WTO Trade in Value-Added (TiVA) Database'. The database links national input–output tables with bilateral trade data to develop inter-country input–output tables that allow compiling, and revealing such chains. Its data are actual nominal values compiled at current exchange rates. The paper takes issue with that choice. Recalling that elsewhere in the United Nations national accounting figures are transformed to purchasing power parity before being compared internationally the paper suggests to follow suit and compile international value-added chains at real exchange rates, as well, and it sketches an introductory outline of how to do so.